PP14 An investigation of ambulance clinical recommendations for the management of obstetric emergencies in Australia and New Zealand. Issue 9 (19th August 2021) - Flanagan, Belinda; Pearce, James; Barr, Nigel; Eastwood, Kathryn
Abstract : Background: Various international studies have recognised that paramedics receive limited obstetric training and historically lack confidence in managing obstetric and neonatal emergencies. This lack of confidence, deficits in training and limited exposure to such cases may be sustained by absent, dated or insufficient clinical guidance provided by the employer. Clinical guidelines are an essential tool and cognitive aid to provide guidance when formulating an appropriate treatment plan, however paramedics have reported the use of varying and dated practices and procedures that have the potential to cause significant patient harm. The aim of this study was to conduct a qualitative textual/document analysis on five publicly available obstetric guidelines published by ambulance services in Australia and New Zealand. Method: Publicly available electronic guidelines from Australian and New Zealand ambulance jurisdictions were imported into a custom designed data collection frame for comparison. This frame focused on five specific areas of obstetric presentations. Guideline quality was measured against a recognised national standard for the development and publication of clinical guidelines. Information and recommendations presented were compared against expert advice provided by the Royal Australian and New Zealand College of Obstetrics and Gynaecology (RANZCOG), Word Health Organization (WHO), state health clinical guidelines and systematic reviews. Results: All ambulance service guidelines reviewed failed to meet the national standards for the development and publication of clinical guidelines in the area of transparency and grading of evidence. Some advice within the guidelines was found to be inconsistent, not supported by evidence, have the potential to cause harm or be absent. Some were found to be heavily reliant on hospital-based mnemonics that were either not ambulance specific or contained advice that was outside a paramedic scope of practice. Conclusion: This study has identified inconsistent recommendations and highlighted conflicting and inadequate advice for paramedics when managing obstetric and neonatal emergencies.